2021
DOI: 10.1007/s10792-021-02052-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Immulite® TSI immunoassay for thyroid-associated orbitopathy in patients with recently diagnosed Graves’ hyperthyroidism

Abstract: Purpose The ImmuliteÒ thyroid stimulating immunoglobulin (TSI) immunoassay is a relatively new commercial assay that has shown good diagnostic accuracy in Graves' hyperthyroidism (GH). However, its clinical utility in thyroid-associated orbitopathy (TAO) is less clear. The purpose of this study was to assess the diagnostic accuracy of the ImmuliteÒ TSI immunoassay for TAO and investigate the associations between TSI and other clinical measures. Methods One hundred and forty patients that had been diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Interestingly, although the bridge-based assay presumably detects TSI more specifically than TBII assays, studies found that TBII assays correlate equally or even stronger with disease activity than the bridge-based assay ( 26 , 30 ). Furthermore, our study did not find any correlation between bridge-based TSI levels and the severity of the disease, which is consistent with some previous reports ( 26 , 28 ), but differing from another ( 27 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, although the bridge-based assay presumably detects TSI more specifically than TBII assays, studies found that TBII assays correlate equally or even stronger with disease activity than the bridge-based assay ( 26 , 30 ). Furthermore, our study did not find any correlation between bridge-based TSI levels and the severity of the disease, which is consistent with some previous reports ( 26 , 28 ), but differing from another ( 27 ).…”
Section: Discussionsupporting
confidence: 92%
“…Research herein has primarily focused on the use of different assays as a biomarker for disease activity and severity, showing that TSI bioassays, outperform TBII assays (4,5,7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). So far, only a limited number of studies investigated the applicability of the bridge-based TSI binding assay as a biomarker for disease activity and severity in GO, with conflicting results (26)(27)(28)(29)(30). Although identifying patients with active disease is important, it may be even more relevant to identify patients who will not respond to intravenous methylprednisolone (IVMP).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in line with a newly published study from Australia [34], in which 140 participants recruited of which 75 (53.6%) had GO. Although Immulite TSI level was higher in the presence of GO, it showed poor diagnostic accuracy and no correlation with clinical markers of GO severity or activity.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…The changes of Fa value of MS lesions in different periods have their own characteristics. The accumulation of inflammatory cells and myelin disintegration products potentially limits the diffusion of water molecules, forming a diffusion barrier without directional water molecules, resulting in the decrease of FA value [ 12 ]. Giordano et al found that DTI imaging technology has characteristics of brain endoplasmic injury in toxic encephalopathy.…”
Section: Literature Reviewmentioning
confidence: 99%